ANALISIS PELUANG PASAR PRODUK FROZEN FOOD PADA TOKO RIZKI FROZEN FOOD DI SIMPANG BANDAR SETIA - Haikal Rizki Pratama; Gita Gita; Irwan Saleh Harahap (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the marketing strategies used by the Rizki Frozen Food store in Simpang Bandar Setia to increase consumer purchasing interest. A descriptive qualitative research approach was used through interviews, observation, and documentation to obtain a comprehensive overview of the marketing activities undertaken. The results show that the implementation of the marketing mix, which includes product, price, promotion, and place aspects, plays a significant role in influencing consumer interest in the frozen food products offered. In terms of products, the store is able to provide food choices that follow evolving consumer needs, have a variety of flavors, and match consumer preferences. A competitive and affordable pricing strategy strengthens consumers' perceptions of product quality. Meanwhile, promotions through social media such as Instagram, TikTok, and Facebook have proven to be the most dominant factor because visual content and collaboration with local influencers have been able to expand marketing reach and influence consumer purchasing decisions. On the other hand, the neat store layout, comfortable shopping space, and easily accessible location also create a positive experience that encourages consumers to make repeat purchases. Overall, the research findings confirm that the marketing strategy implemented by the Rizki Frozen Food store in Simpang Bandar Setia is effective in increasing purchasing interest, particularly through optimizing digital media and providing products relevant to customers' needs. These findings are expected to serve as a reference for other businesses in formulating more competitive and sustainable marketing strategies amidst the ever-growing competition in frozen food sales.